Thermostable power sensors for transmitted continuous radiation of CO- and CO₂- lasers - Zagoruiko, Yu.A.; Kovalenko, N.O.; Fedorenko, O.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Thermostable power sensors for continuous and pulsed periodic laser IR radiation are developed. Manufactured are scale models for a multifunctional optical element which combines the functions of transmitting radiation sensor and output laser window. Technical characteristics of the developed sensors are presented; the possibilities of their use in technological CO₂ - laser units are discussed.